INFLUENCE OF APOPTOSIS-INDUCED MESENCHYMAL STEM CELLS ON RENAL FUNCTION IN EXPERIMENTAL ACUTE RENAL FAILURE - Чеботарьова, А.А. (World of Medicine and Biology, 2016)
The article presents the measuring of nitrogen metabolism products level in the blood of rats undergoing experimental acute renal failure, and changes in these indicators on the background of an injection mesenchymal stem cells cultured in the apoptosis-induced environment. Stem cells from bone marrow were obtained from normal rats and cultured with standard medium with adding the homogenate of kidney tissue after acute renal failure, thus creating apoptosis-induced conditions. The data show a increase nitrogen metabolism products in the blood of animals with acute renal failure. Intravenous injection of a suspension of the animal mesenchymal stem cells significantly improved biochemical indices of the blood of animals.
Keywords: acute renal failure; mesenchymal stem cells; apoptosis; creatinine; urea